The effect of the JOBS act on analyst coverage of emerging growth companies. Issue 1 (11th January 2019) - Precourt, Elena
Abstract : Purpose: The purpose of this paper is to examine the section of the Jumpstart Our Business Startups (JOBS) Act related to information dissemination by sell-side security analysts. The paper analyzes how the abolishment of the quiet period requirements for emerging growth companies (EGCs) changes the analyst initiation timing and market expectation of and reaction to the issuance of the analyst recommendations. Design/methodology/approach: This paper considers the effect of the abolishment of the quiet period requirements on analyst coverage initiations for EGCs with IPOs between January 2006 and December 2015 using regression analyses and probability models. Findings: The results confirm the current anecdotal and empirical evidence that a shorter, de facto, quiet period exists. Analyst issue stronger average ratings for EGCs than for similar firms with IPOs before the JOBS Act. EGCs with initiations from multiple analysts also experience stronger positive market reaction than the firms with initial offerings before the JOBS Act. The market seems to anticipate which EGCs will have initiations and particularly which EGCs will have initiations from multiple analysts. The investors, however, do not fully anticipate the strength of actual recommendations. Practical implications: This paper is important for researchers, practitioners and policy-makers to understand how analysts impact the financial markets, how timing of analyst initiations affects stock prices of EGCs and what firm characteristics play a role in securing analyst coverage shortly after initial offerings. Originality/value: This paper adds to the emerging literature on consequences of and changes brought by the JOBS Act. Specifically, this paper extends the limited literature on analyst initiations issued for firms with IPOs following the JOBS Act, timing of those initiations and magnitude of the market's response to the initiations.